Real & Simulated QPSK Up-Converted Signals by a Sampling Method Using a Cascaded MZMs Link - Hassan Termos; Ali Nansour (Photonics, 2022)
This study focuses on a novel concept of transmitting of a quadrature phase shift keying (QPSK) modulation by an electro-optical frequency up-conversion using a cascaded Mach–Zehnder modulators (MZMs) link. Furthermore, we conduct and compare the results obtained by simulations using the Virtual Photonics Inc. (VPI) (Berlin, Germany) simulator and real-world experiments. The design and operating regime peculiarities of the MZM used as a sampling up-converter mixer in a radio over fiber (RoF) system are also analyzed. Besides, the simulation and experimental results of static and dynamic characteristics of the MZM have approximately the same behavior. The conversion gain of the cascaded MZMs link is simulated over many mixing frequencies and it can decrease from 17.5 dB at 8.3 GHz to −4.5 dB at 39.5 GHz. However, in real world settings, it may decrease from 15.5 dB at 8.3 GHz to −6 dB at 39.5 GHz. The maximum frequency range is attained at 78.5 GHz for up-conversion through simulations. Error vector magnitude (EVM) values have been done to evaluate the performance of our system. An EVM of 16% at a mixing frequency of 39.5 GHz with a bit rate of 12.5 Gbit/s was observed with the considering sampling technique, while it reached 19% in real-world settings with a sampling frequency of 39.5 GHz and a bit rate of 12.5 Gbit/s.